Relevance of Imam Abu Hamid Al-Ghazali's Thoughts to the Reformation of Learning in Nigeria - Suraju, Saheed Badmus; Adebayo, Yunus Ibikunle (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2024)
The Islamic perspective of education is the harmonization between sense, mind and religious faith to build a complete and an ideal personality in an Islamic environment. However, the contemporary learners in Nigeria are not only reducing in moral but also religious teachings which are the core values in personality development. Series of questions could be raised as per the reason behind the reduction of Nigeria system of learning in achieving its core objective in the learners especially among the Muslims. By this, the teacher, the learners and the system are needed to be scrutinized for possible response in rebuilding the Nigerian learning system. It is therefore the aim of this paper to investigate the philosophical thoughts of Abu Hāmid Al-Ghazālī and their relevance to reformation of learning in Nigerian. In achieving this, the paper adopts historical and analytical methods of research. The historical method has assisted in accounting for the biography of Al-Ghazālī while analytical method has been used to explain the philosophical thoughts of Al-Ghazālī in relation to how they can be used to reform learning system in Nigerian society. This will assist in reclaiming the early Muslim identity in learning. The paper reveals that the Nigerian learning system is suffering a taste of spirituality by focusing more on materialism. The paper concludes that spirituality is needed in ensuring better change in the life of the learners. The paper, therefore, recommends the incorporation of Imam Al-Ghazālī’s thoughts into the learning curriculum of the Muslim Youths across all levels of education.